The Epistemic Status of Divine ‘Non-Intervention’: A Theological Analysis of Passive Decree (al-Qaḍāʾ al-Sākin) and Its Implications for Human Moral Responsibility in Sunni Kalām - Umer Majeed; Dr. Zia ul Haq (AL-IDRAK JOURNAL, 2025)
This study investigates the epistemic and theological dimensions of divine non-intervention (al-qaḍāʾ al-sākin) within the Sunni kalām tradition, focusing on its implications for human moral responsibility. It explores how the notion of a “passive decree” articulates a form of divine volition that refrains from direct intervention while preserving God’s omnipotence, justice, and wisdom. By examining Ashʿarī, Māturīdī, and Atharī frameworks, the research analyzes the conceptual distinctions between active divine will, permissive allowance, and tacit approval, and how these distinctions shape understandings of human agency, accountability, and ethical obligation. The study also addresses the epistemic challenges inherent in discerning divine non-intervention: the limits of human reason (naẓar), the role of revealed knowledge, and the interpretive frameworks used to distinguish divine silence from explicit intervention. It further examines the interplay between passive decree and theodicy, considering natural disasters, systemic injustice, and morally consequential human actions. Through a comparative analytical approach, the paper demonstrates that Sunni kalām traditions conceptualize non-intervention as both a metaphysical and ethical category. Ashʿarī occasionalism emphasizes continuous divine creation of all acts, preserving moral responsibility through kasb (acquisition), while Māturīdī frameworks highlight stable divine customs (ʿādāt Allāh) that allow for genuine human agency. Atharī perspectives prioritize scriptural affirmation of divine will without constructing intermediate categories of passive decree. The findings reveal that passive decree operates at the intersection of divine omnipotence, human moral responsibility, and epistemic limitation, offering a coherent theological account of how God’s non-intervention shapes ethical deliberation and human accountability in a contingent world.